Load Frequency Control in Microgrid Using Fuzzy Logic Table Control - Mazin Mustafa , Mahdi; Abu Zaharin, Ahmad (IEEE, 2016)
This paper presents the load frequency control in isolated ac microgrid using fuzzy logic table control. The objective of load frequency control is to hold the frequency constant against any load changes. The main task of microgrid is to maintain the voltage level supply to the loads. Any mismatch between the power generations and loads create to the major problem of frequency fluctuation that effected to the active power sharing and reliability in microgrid power flow. In this paper, the model of the generation unit in microgrid is carried out for proposing the load frequency control using fuzzy logic table. The comparison of the proposed method is compared with the common proportional integral (PI) controller. The simulation results have shown that the proposed method is better than PI controller in term of transient performance. The simulation is carried out through the Matlab/Simulink environment.